Self Protective Behavior of Leprosy Family Members in Narathiwat Province - Santhikarn, Patchinee; Tongsamsi, Isara; Tansakun, Kanlaya (Princess of Naradhiwas University Journal, 2019)
This correlation research aimed toanalyze the causal relation between, in one hand, the knowledge, attitude as well as prevention behaviortoward leprosy (exogenous latent variable)and, in the other hand, self-protection behavior in family members of Leprosy patients (endogenous latent variable) in Narathiwat province. The moderated mediation models were personal factors in leprosy family members: gender, age, income, size of family as well as family type of leprosy patients. Sample was 110 family members of patients with leprosy (15 family members of patients with leprosy more than one time, and 95 family members of patients with leprosy only one time). The sample must live with the leprosy patient in the same home more than 5 days a week, at least6 months, and age over 18 years old.And they were selected using the sample criteria for multivariate analysis,as in the form of the least squares parametric equations from Hair, Hult, Ringle, and Sarstedt (2014). The research found that personal factors data in age and income had nostatistically significant relationship at .05 with self-protection behaviors. The sex and size of the family and family characteristics for self-protection behaviors were not statistically significant at the level of .05. An analysis of the causal relation between the knowledge of leprosy and attitude toward leprosy prevention behavior on self-protection behaviors found that the knowledge of leprosy was not directly affected by the leprosy behavior of leprosy family members at a statistically significant of .01.The attitudes toward leprosy had a direct influence on the leprosy prevention behavior of leprosy family members at the statistically significant level of .0.1.And knowledge about leprosy and attitudes towards leprosy could explain the prevalence of leprosy behavior in leprosy family members at the level of 39.4%.